New network structures from Cu(II) complexes of chelating ligands with appended hydrogen bonding sites - Prior, Timothy; Stephenson, Maria D.; Prior, Timothy J.; Hardie, Michaele J. (CRYSTAL GROWTH & DESIGN, 2008)
Complexes [Cu(phenpyzda)Cl-2(H2O)]center dot H2O (1) and [Cu(phenpyzda)Br-2(H2O)]center dot 2H(2)O (2), where phenpyzda = pyrazino[2,3-f][1,10]phenanthroline-2,3-diamide, show similar molecular structures with square planar Cu(II). Each complex has a complicated three-dimensional (313) hydrogen bonding network with I having an unusual 3,9-connectivity. Use of the corresponding carboxylic acid, pyrazino[2,3-f][1,10]phenanthroline-2,3-dicarboxylic acid, results in the unexpected conversion of the ligand to 1H,3H-imidazol[2,3-f][1,10]phenanthroline (= imiphen) in the complex [CuCl3(imiphenH)] center dot 2H(2)O, which has a 3D hydrogen bonded network structure of 3,6-connectivity. The more extended phenanthroline-based ligand 1,10-phenanthroline-5,6-[pteridine-2,4-diamine] was also synthesized, but no crystalline complexes of it were isolated. [Cu(bpy4diol)(2)](NO3)(2)center dot H2O (4), where bpy4diol = 2,2'-bipyridine-4,4'-diol, shows a two-dimensional (2D) hydrogen bonded network with hexagonal topology. [Cu(bpy4da)(NO3)(2)] (5) where bpy4da = 2,2'-bipyridine-4,4'-diamine has a 3D 2-fold interpenetrating alpha-Po related hydrogen bonded structure. Complexes [Cu(bpy4da)Cl-2] (6) and [Cu(bpy5dmol)Cl-2] (7) where bpy5dmol = 2,2'-bipyridine-5,5'-bis(hydroxymethyl) have similar chloro bridged coordination chains that hydrogen bond together into 3D and 2D networks, respectively. Despite their different hydrogen bonding patterns, complexes 6 and 7 are isomorphic.
Batch 005. Output ID 36374.
Keywords: metal-organic frameworks coordination polymer pi-stacking magnetic characterization 3-dimensional network molecular tectonics building units acid 3; 3'-dihydroxy-2; 2'-bipyridine cobalt